Behçet’s Disease: An Overview of Etiopathogenesis - Leccese, Pietro; Alpsoy, Erkan (Frontiers in Immunology, 2019)
Behçet's disease (BD) is a systemic inflammatory disease with a chronic, relapsing-remitting course of unknown etiology hallmarked predominantly by mucocutaneous lesions and ocular involvement. BD shares some common features with autoimmune and autoinflammatory diseases and spondyloarthropathies (MHC-I-opathies). It is related to more than one pathogenic pathway triggered by environmental factors such as infectious agents in genetically predisposed subjects. The interplay between genetic background and immune system is linked to the BD presentation. Genetic factors have been investigated extensively, and several recent genome-wide association studies have confirmed HLA-B*51 to be the strongest genetic susceptibility factor. However, new non-HLA susceptibility genes have been identified. Genetic variations in the genes encoding the cytokines could affect their function and be associated with disease susceptibility. Infectious agents such as Streptococcus sanguinis or the differences in salivary or gut microbiome composition can be considered to trigger the innate-derived inflammation, which is, subsequently, sustained by adaptive immune responses. Altered trimming of microbial and/or endogenous peptides by endoplasmic reticulum aminopeptidase 1 (ERAP1), presented by HLA-B*51, may play a key role in BD pathogenesis causing an alteration in T cell balance with downregulation of Tregs and expansion of Th1 and Th17. The activity of neutrophils is increased and there is an intense neutrophil infiltration in the early stage of inflammation in organs affected by the disease. Association with HLA-B*51 and increased IL-17 response seems to have an important role in neutrophil activity. In this paper, we provide an overview of the most recent advances on BD etiopathogenesis.